EFEKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN NANGKA (Artocarpus heterophyllus L) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - D. Elysa Putri Mambang; Jafril Rezi (Universitas Quality, 2018)
This study aims to determine whether the Ethanol Extract of Jackfruit Leaves has antibacterial properties and to determine the concentration of Ethanol Extract of Jackfruit Leaves which is useful as an antibacterial to the growth of Staphylococcus aureus bacteria. The samples tested in this study were young jackfruit leaves (not too young). Fresh jackfruit leaves weighed 1000 g, dried jackfruit leaves, 386.06 g and mashed jackfruit leaves 232.12 g and weighed 200 g. The results of research conducted from testing Ethanol Extract of Jackfruit Leaves on the growth of Staphylococcus aureus bacteria can be concluded that: Ethanol Extract of Jackfruit Leaf (Artocarpus heterophyullus L) has an antibacterial effect on the growth of Staphylococcus aureus bacteria at 50% concentration.